2013
DOI: 10.1136/bjophthalmol-2013-303939
|View full text |Cite
|
Sign up to set email alerts
|

All biometric components are important in anisometropia, not just axial length

Abstract: Axial length asymmetry has the strongest correlation with anisometropia; nonetheless, other components of ocular biometrics such as corneal power, lens opacity, lens power and anterior chamber depth are related to anisometropia as well. More than 10% of changes in anisometropia can be explained with changes in factors other than asymmetry of ocular biometrics and lens opacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
24
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 20 publications
9
24
2
Order By: Relevance
“…The correlations of the measured parameters in our study were parallel with those of Hashemi et al (2013). The correlations of the measured parameters in our study were parallel with those of Hashemi et al (2013).…”
Section: Anisosrsupporting
confidence: 84%
See 4 more Smart Citations
“…The correlations of the measured parameters in our study were parallel with those of Hashemi et al (2013). The correlations of the measured parameters in our study were parallel with those of Hashemi et al (2013).…”
Section: Anisosrsupporting
confidence: 84%
“…They found that asymmetry of CR, ACD, lens thickness, lens power, vitreous length and AL were all significantly more prevalent among anisometric than isometropic subjects. The correlations of the measured parameters in our study were parallel with those of Hashemi et al (2013). However, our correlation coefficients were lower and no significant correlation was observed between Ani-soACD and AnisoSE.…”
Section: Anisosrsupporting
confidence: 68%
See 3 more Smart Citations